The company in Peru: Classification and corporate social responsibility - Trigoso Suárez, Marco Antonio (2019)
The purpose of this investigation is to share with law students and readers in general, some clarifications on the classification of the company and, corporate social responsibility in Peru. The method I have used in this investigation is the Descriptive, the first step to obtain accurate and collected information of the specialized doctrine and legislation, and then organize and classify it systematically with respect to the object of study, thus achieving the results sought. The main results are: to have a short tool, structured and easy access to technical information, for law students and any reader, regarding the classification of the company and, corporate social responsibility in Peru. And, for those who are about to start a business activity, be a simple guide that contributes to the possibility of obtaining a better result in their entrepreneurship. Conclusions of the study, a clear classification was established regarding the different modalities of companies and corporate social responsibility in Peru. This is also a means of contributing to the formalization of the sector and which the country so badly needs.